Problem-based learning model implementation to improve students problem-solving skills - Nur Dalilatul Hayaro Indra Waskita; Beni Setiawan; Muhamad Arif Mahdiannur (Jurnal Pijar Mipa, 2022)
This research aims to improve students' problem-solving skills about additives in food and beverages. This study used one group pretest and posttest design. This study involved thirty-one students from grade 8 at one of the state junior high schools in Gresik Regency, East Java, for the 2021/2022 Academic Year. Data collection techniques using observation assessment sheets, written test assessment sheets, and response questionnaire forms. Based on this study, the results of the percentage of learning implementation of the first meeting of the first session were 91%, the first meeting of the second session was 94%, the second meeting of the first session was 92%, and the second meeting of the second session was 95% by meeting the excellent category. The problem-solving skills were obtained n-gain 0.78 high categories, including the stage of formulating the question 0.67 medium categories, the hypothesis  0.57 with the medium category, determining the solution obtained 0.83 with the high category. The calculation of n-gain in each stage obtained an average n-gain of 0.74 by fulfilling the high category—the response questionnaire form from students with a percentage with excellent categories and positive student responses. The results of this study show that implementing problem-based learning can improve problem-solving skills, especially additives in food and beverages.